Factors Related to Multidimensional Frailty Among Hispanic People Living With HIV Aged 50 Years and Above: A Cross-sectional Study - Iriarte, Evelyn; Cianelli, Rosina; De Santis, Joseph P.; Alamian, Arsham; Castro, Jose Guillermo; Matsuda, Yui; Araya, Alejandra-Ximena (The Journal of the Association of Nurses in AIDS Care, 2023)
Among Hispanics, frailty has been extensively studied as a physical syndrome associated with an increased risk for adverse outcomes. Because of additional barriers to accessing care, the impact of frailty may be even more significant for people living with HIV (PLWH). Multidimensional frailty among Hispanic PLWH has not been studied. This study aimed to examine the factors related to multidimensional frailty among Hispanic PLWH aged 50 years and above. A cross-sectional design with 120 participants was used. Hypothesized factors related to multidimensional frailty were sociodemographic and psychosocial variables. Multidimensional frailty was measured with the Tilburg Frailty Indicator. We found that 45.83% of the participants were frail ( n = 55), and multidimensional frailty was significantly associated with higher depressive symptoms ( b = .26, p < .001) and a higher number of comorbidities ( b = .71, p < .001). This study identified factors that clinicians should be aware of when caring for Hispanic PLWH to prevent or manage frailty-related complications.